Changes in Staphylococcus aureus susceptibility across Latin America between 2004 and 2010 - Garza-González,Elvira (2013)
The Tigecycline Evaluation and Surveillance Trial is a global surveillance study monitoring the efficacy of tigecycline and comparators against clinically important pathogens. Between 2004 and 2010, 3126 isolates of Staphylococcus aureus were collected from 66 centers in 13 countries in Latin America; of these, 1467 (46.9%) were resistant to methicillin. The main contributors of S. aureus isolates were Mexico (n = 846), Argentina (n = 740), and Colombia (n = 445). The methicillin-resistant S. aureus rate was greater than 50% in five countries, the highest reported in Puerto Rico (73.9%). Methicillin-resistant S. aureus rates across Latin America ranged from 40.1% to 50.6% over the study period. All S. aureus isolates were susceptible to linezolid and vancomycin, while 100% of methicillin-susceptible S. aureus isolates and 99.8% of methicillin-resistant S. aureus isolates were susceptible to tigecycline. Both methicillin-susceptible S. aureus and methicillin-resistant S. aureus were highly susceptible to minocycline (99.2% and 97.0%, respectively). Latin American methicillinsusceptible S. aureus were highly susceptible to levofloxacin (94.6%) while only 16.2% of methicillin-resistant S. aureus were levofloxacin-susceptible. This study shows that linezolid, vancomycin, and tigecycline are all highly active against S. aureus from Latin America, regardless of methicillin resistance.